METHODOLOGY OF LAW ENVIRONMENT: TRYING TO UNDERST AND THE PROBLEM AND DEVELOPMENT CONCEPTS - Дручек, Олена Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: an attempt was made to analyze some problems of functioning of the methodology of national law and to identify the main directions of its development. Research methods: phenomenological, comparative-legal, formal-legal, dialectical, sociological, prognostic. Results: the content of particular problems of the national methodology of jurisprudence is identified and revealed. Prospective directions of further theoretical and legal researches of problems of methodology of jurisprudence are substantiated. It is proved that the analysis of problems of functioning and development of legal science in Ukraine and determination of the most innovative directions of its methodology is necessitated by the need to increase the potential of legal science to solve many problems of modern Ukrainian society and the development of domestic legal science. It is substantiated that the contradictions in the methodology of jurisprudence are caused by various factors, and the basic concepts are connected with problems of development of society, science, law, legal system in the new socio-economic, political conditions and changes in the system of values and world outlook of society. It is proposed to differentiate the content and scope of the concepts of «jurisprudence methodology» and «methodology of law» on the basis of representations of jurisprudence as a science with characteristic methods of cognition and law with the inherent system of methods of legal regulation. Opinion on the allocation of the system of methods of jurisprudence: 1) general (philosophical) methods; 2) general scientific methods; 3) private scientific methods; 4) special methods. The problem of internal organization of jurisprudence methodology is investigated. It is proposed to distinguish in its structure the following components: 1) instrumental; 2) constructive; 3) internal organizational. The main shortcomings of the internal organization of the methodology of jurisprudence are identified. It is proved that the basic directions of development of methodology of law depend on the concept of understanding of law. The tendency of priority of integrative legal understanding of law and socialization of legal knowledge is established. The expediency of development of methodological researches within the limits of sociological-integrative approach is substantiated. The prospects of expanding the categorical-conceptual apparatus of jurisprudence by transforming the doctrinal concepts into legal ones and introducing new concepts and categories formed and separated in the legal sciences and branches of law are determined. Innovative methods of researching the problems of law have been characterized and identified as effective methods such as: synergistic, hermeneutics, case method, abductions and others. Discussion: search for new rational ways of solving existing problems of functioning and internal contradictions of jurisprudence methodology.